Effectiveness of linkage to care and prevention interventions following HIV self-testing: a global systematic review and meta-analysis protocol. Issue 9 (8th September 2022) - Bain, Luchuo; Amu, Hubert; Dowou, Robert Kokou; Memiah, Peter; Agbor, Valirie Ndip
Abstract : Introduction: Early identification of persons living with HIV (PLWH) is crucial to institute timely treatment to prevent HIV-related morbidity and mortality. The convenience, flexibility and confidentiality of HIV self-testing enhance the acceptability of HIV testing and early detection of PLWH. However, persons who tested positive after a self-test are more likely to present late for treatment. This review seeks to evaluate the effectiveness of interventions to improve linkage to care and prevention after self-testing. Methods and analysis: We will search PubMed, Embase, Web of Science, Cochrane Library, PsycInfo, Global Health Library, ClinicalTrials.gov and current controlled trials for all randomised and non-randomised studies published from 1 January 2010 to 31 July 2022 without language restriction. Two review authors will independently screen and select articles (based on the eligibility criteria for this review), extract data and assess the risk of bias in the included studies. Study-specific estimates will be converted to log risk ratios and weighted by the inverse of the variance of the log risk ratio before pooling into a fixed-effect model. The Cochrane's Q χ 2 test and the I 2 statistic will be used to assess and quantify heterogeneity in the included studies, respectively. The Egger's test and funnel plots will be used to assess publication bias. Sensitivity analysis will be conducted using leave-one-out analysis to assess the impact of outliers on the overall summary intervention effect. Ethics and dissemination: No ethical clearance is needed for the current study as it will be based on already published articles. We will publish the findings of this study in international peer-reviewed journals and present them at conferences.